2012
DOI: 10.7120/096272812x13345905673809
|View full text |Cite
|
Sign up to set email alerts
|

Do dog owners perceive the clinical signs related to conformational inherited disorders as ‘normal’ for the breed? A potential constraint to improving canine welfare

Abstract: Selection for brachycephalic (foreshortened muzzle) phenotypes in dogs is a major risk factor for brachycephalic obstructive airway syndrome (BOAS). Clinical signs include respiratory distress, exercise intolerance, upper respiratory noise and collapse. Efforts to combat BOAS may be constrained by a perception that it is 'normal' in brachycephalic dogs. This study aimed to quantify ownerperception of the clinical signs of BOAS as a veterinary problem. A questionnaire-based study was carried out over five month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
165
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(170 citation statements)
references
References 24 publications
3
165
1
1
Order By: Relevance
“…A recently published study showed a disparity in recognition and perception of clinical signs associated with brachycephaly in dogs. Dog owners reported a high frequency and severity of respiratory signs but did not perceive them as problems (Packer et al, 2012). We tried to address this by asking questions that used objective criteria, such as time needed for recovery and questions about activities that could easily be observed by a dog owner.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study showed a disparity in recognition and perception of clinical signs associated with brachycephaly in dogs. Dog owners reported a high frequency and severity of respiratory signs but did not perceive them as problems (Packer et al, 2012). We tried to address this by asking questions that used objective criteria, such as time needed for recovery and questions about activities that could easily be observed by a dog owner.…”
Section: Discussionmentioning
confidence: 99%
“…Brachycephalic dog breeders gave even higher importance to Dam Genetics and Health than breeders of non-brachycephalic dog breeds. It is assumed that breeders of brachycephalic dogs are aware of the problems associated with these breeds of dogs (e.g., obstructive airway syndrome (BOAS) is a common constraint for brachycephalic breeds [43]), and therefore place more importance on additional genetic and health aspects which may also be present. Genetic testing was more relevant to some breeds than others, likely reflecting known issues within the breed.…”
Section: Discussionmentioning
confidence: 99%
“…Breeds with elongated noses (mesocephalic breeds) have more olfactory receptor cells, allowing them to identify and retain more scent (Craven et al, 2007;Abney, 2009). Brachycephalic breeds also typically have breathing issues, resulting in less oxygen provision to the brain causing the dogs to tire easily (Rauth-Widmann, 2006;Packer et al, 2012;Bartels et al, 2015). Brachycephalic breeds should therefore be avoided when selecting a detection dog.…”
Section: 2mentioning
confidence: 99%